Key Audit Matters, Audit Delay, Earning Management, dan Kualitas Audit: A Systematic Review - Devi Nurcahya; Rizdina Azmiyanti (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2025)
This study aims to review previous literature on the impact of KAM implementation on Audit Delay, Earning Management, and Audit Quality. The method used is a systematic literature review, with articles obtained through the Publish or Perish application. The article criteria are articles indexed by SINTA and Scopus published in 2022-2025. The results of the study indicate that disclosure of Key Audit Matters can improve the quality of financial report communication and transparency so that it has a negative effect on audit delay, and can reduce the potential for earnings management. Disclosure of Key Audit Matters also shows a positive effect on audit quality because of broader disclosure, information asymmetry between stakeholders and management can be overcome